2015
DOI: 10.1016/j.ijpddr.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

In vitro flubendazole-induced damage to vital tissues in adult females of the filarial nematode Brugia malayi

Abstract: The use of a microfilaricidal drug for the control of onchocerciasis and lymphatic filariasis necessitates prolonged yearly dosing. Prospects for elimination or eradication of these diseases would be enhanced by availability of a macrofilaricidal drug. Flubendazole (FLBZ), a benzimidazole anthelmintic, is an appealing candidate macrofilaricide. FLBZ has demonstrated profound and potent macrofilaricidal effects in a number of experimental filarial rodent models and one human trial. Unfortunately, FLBZ was deeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 29 publications
(42 reference statements)
3
33
0
Order By: Relevance
“…In the current study, we used the RNAseq approach to identify significant genes and biological processes that were being affected in B. malayi when challenged with FLBZ. Analysis of GO terms highlights the influence FLBZ on filarial embryonic development, consistent with previous findings (O'Neill et al., 2015, O'Neill et al., 2016). Significantly enriched GO terms are commonly associated with RNAi phenotypes of embryo/larval lethality or impairments to overall morphogenesis for C. elegans homologues.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the current study, we used the RNAseq approach to identify significant genes and biological processes that were being affected in B. malayi when challenged with FLBZ. Analysis of GO terms highlights the influence FLBZ on filarial embryonic development, consistent with previous findings (O'Neill et al., 2015, O'Neill et al., 2016). Significantly enriched GO terms are commonly associated with RNAi phenotypes of embryo/larval lethality or impairments to overall morphogenesis for C. elegans homologues.…”
Section: Discussionsupporting
confidence: 90%
“…Hypodermal damage is a common theme among the benzimidazoles including FLBZ (Lacey, 1988, Franz et al., 1990a, Kumar and Lai, 1998, Hanser et al., 2003, Shalaby et al., 2009, Cárdenas et al., 2010, O'Neill et al., 2015). Previous studies have shown that short-term exposure to FLBZ leads to extensive damage to B. malayi hypodermal tissue (O'Neill et al., 2015). Given that components of the nematode cuticle are synthesized and delivered to the surface through the hypodermis (Page and Winter 2003), it is not surprising that hypodermal tissue damage would result in a dampening of cuticle synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations